2021
DOI: 10.1101/2021.07.28.454220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learning of Pseudomonas aeruginosa transcriptomes identifies independently modulated sets of genes associated with known transcriptional regulators

Abstract: The transcriptional regulatory network (TRN) of Pseudomonas aeruginosa plays a critical role in coordinating numerous cellular processes. We extracted and quality controlled all publicly available RNA-sequencing datasets for P. aeruginosa to find 281 high-quality transcriptomes. We produced 83 new RNAseq data sets under critical conditions to generate a comprehensive compendium of 364 transcriptomes. We used this compendium to reconstruct the TRN of P. aeruginosa using independent component analysis (ICA). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Compendia can contribute to helping us gain a systems-level understanding of microbial biology. One major goal for systems biology is to model how information is encoded, specifically to reverse engineer the hierarchy of the transcriptomic regulatory network (TRN) [66] , [67] , [68] , [69] , [70] , [71] . Knowing the organization of a regulatory network allows us to control or optimize parts of the system, a necessary step for many biotechnological advances [72] , [73] , [74] , [75] .…”
Section: Why Use Compendia: Benefits and Applications Of Using Compendiamentioning
confidence: 99%
See 2 more Smart Citations
“…Compendia can contribute to helping us gain a systems-level understanding of microbial biology. One major goal for systems biology is to model how information is encoded, specifically to reverse engineer the hierarchy of the transcriptomic regulatory network (TRN) [66] , [67] , [68] , [69] , [70] , [71] . Knowing the organization of a regulatory network allows us to control or optimize parts of the system, a necessary step for many biotechnological advances [72] , [73] , [74] , [75] .…”
Section: Why Use Compendia: Benefits and Applications Of Using Compendiamentioning
confidence: 99%
“…A similar dimensionality reduction analysis was performed applying a sparse autoencoder to a yeast ( S. cerevisiae ) compendium, where Chen et al found latent variables represented pathways and other layers of biological abstractions such as a transcription factor complexes and signaling pathways [83] . In other studies, applying independent component analysis (ICA) to a compendium of transcriptome data revealed transcription modules [68] , [69] , [70] . Specifically, Poudel et al identified differentially active modules in S. aureus that varied based on the growth different media, which revealed metabolic regulators that respond to shifts in nutrients available [69] .…”
Section: Why Use Compendia: Benefits and Applications Of Using Compendiamentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][23][24][25][26] However, how genetic differences translate into differences in the transcriptome and ultimately phenotypes is not well understood. The many transcription factors (TFs) and other transcriptional regulatory elements found in P. aeruginosa control the expression of many gene products that mediate various different traits 27,28 such as virulence [29][30][31] and these can vary across strains. For example, a study by Sana et al found a set of core genes that were differentially expressed in PAO1 compared to PA14.…”
Section: Introductionmentioning
confidence: 99%
“…However, we have demonstrated that iModulons recapitulate known regulatory mechanisms and can thus be considered as knowledge-based representations of the composition of the transcriptome. Indeed, recent studies successfully applied ICA for model bacteria (e.g., E. coli 13 , Bacillus subtilis 11 ) and even less-studied bacteria (e.g., Staphylococcus aureus 12 , Mycobacterium tuberculosis 19 , Sulfolobus acidocaldarius 19 , Pseudomonas aeruginosa 20 ) to unveil their genome-scale TRNs.…”
Section: Introductionmentioning
confidence: 99%